Correlation between dietary information sources and knowledge of adequate diets in Eastern China - Cui, Bin; Wang, Linda Dong-Ling; Wang, Fu Rong; Peng, Jing; Ma, Jian Ying; Chen, Xiang; Xu, Mei Yin; Ke, Jun; Tian, Yi (Frontiers in Public Health, 2022)
Knowledge of adequate diets can improve an individual’s health status. Although previous studies have identified the main resources from which Chinese people acquire dietary knowledge, it is still unclear whether information sources regarding diets (ISRDs) can increase individuals’ knowledge of adequate diets (KAD) and which ISRDs are most effective in conveying KAD to the Chinese population. In this study, we interviewed 4710 residents in eastern China regarding their ISRDs and KAD. Descriptive statistics, ANOVA, and multivariate linear regression were used to analyze the effectiveness of different ISRDs in transmitting KAD to Chinese individuals and to determine the relationship between ISRDs and KAD. Results showed that the KAD scores of the respondents were low overall. Providing dietary information through expert lectures, books, newspapers, magazines, and social media could significantly improve the average KAD score of Chinese individuals. Respondents with a greater number of ISRDs were more likely to have higher KAD scores. These findings suggest that the number of ISRDs should be increased. In particular, emphasis should be placed on the role of expert lectures, books, newspapers, magazines, and social media.